PENCABUTAN HAK OPSI DALAM PERKARA WARIS BAGI WARGA NEGARA INDONESIA YANG BERAGAMA ISLAM - leliyah leliyah (IAIN Syekh Nurjati Cirebon, 2017)
Based on the General Explanation of Law No. 7 of 1989 on Religious Judiciary that for the litigants regarding inheritance be given the right to legal option to settle the case. Choice of law arises because of the inheritance law pluralism in Indonesia, namely Customary Inheritance Law, Western (Dutch) Inheritance Law and Islamic Inheritance Law. However, after the enactment of Law No. 3 In 2006, the process of the settlement of inheritance for Muslims should be completed in the Religious Court, so there is no further option rights. This paper reviews the existence of option rights in the Religious Judiciary Law and the developments after the enactment of the 2006 amendments.